2006
DOI: 10.1002/adfm.200500361
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Charge‐Carrier Transport in Thin Films of Spiro‐Linked Compounds and Their Corresponding Parent Compounds

Abstract: The charge‐transport properties of the spiro‐linked compounds 2,2′,7,7′‐tetrakis(diphenylamino)‐9,9′‐spirobifluorene, 2,2′,7,7′‐tetrakis(N,N′‐di‐p‐methylphenylamino)‐9,9′‐spirobifluorene, 2,2′,7,7′‐tetra(m‐tolyl‐phenylamino)‐9,9′‐spirobifluorene, and 2,2′,7,7′‐tetra(N‐phenyl‐1‐naphthylamine)‐9,9′‐spirobifluorene, and their corresponding parent compounds, N,N,N′,N′‐tetraphenylbenzidine, N,N,N′,N′‐tetrakis(4‐methylphenyl)benzidine, and N,N′‐bis(3‐methylphenyl)‐(1,1′‐biphenyl)‐4,4′‐diamine, N,N′‐diphenyl‐N,N′‐bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
87
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 24 publications
1
87
0
1
Order By: Relevance
“…MeO-TPD and NPB have very low glass transition temperatures (67 and 95 C, respectively), which is known to lead to undesired crystallization of the material in thin films. 18 Spiro-TTB and BF-DPB instead provide higher stability with glass transition temperatures of 146 and 160 C, respectively. Compared to MeO-TPD and Spiro-TTB, BF-DPB and NPB have higher ionization potentials (IP) (5.23 and 5.4 eV) and BF-DPB and Spiro-TTB provide the highest hole mobility (5.7 Â 10 À5 cm 2 /(V s)).…”
Section: -14mentioning
confidence: 99%
“…MeO-TPD and NPB have very low glass transition temperatures (67 and 95 C, respectively), which is known to lead to undesired crystallization of the material in thin films. 18 Spiro-TTB and BF-DPB instead provide higher stability with glass transition temperatures of 146 and 160 C, respectively. Compared to MeO-TPD and Spiro-TTB, BF-DPB and NPB have higher ionization potentials (IP) (5.23 and 5.4 eV) and BF-DPB and Spiro-TTB provide the highest hole mobility (5.7 Â 10 À5 cm 2 /(V s)).…”
Section: -14mentioning
confidence: 99%
“…field-effect transistors, [9][10][11][12] and lasers. [13][14][15][16][17][18] We recently reported that the charge transport properties in thin films of spiro-linked compounds based on the 9,9′-spirobifluorene core are slightly different with respect to their corresponding parent compounds.…”
mentioning
confidence: 99%
“…These HTMs are standard organic light-emitting diode (OLED) materials due to their superior stability and high glass transition temperatures (T g ). [16,17] The energy levels of the dopant and the hosts are determined using a combination of ultraviolet and inverse photoemission spectroscopy (UPS, IPES). Doping efficiency is assessed through Fermi level shift and current-voltage measurements as a function of incorporated dopant concentration.…”
mentioning
confidence: 99%